Transcapsular arterial neovascularization of liver transplants increases the risk of intraoperative bleeding during retransplantation. (25th January 2013) - Herrmann, Jochen; Herden, Uta; Ganschow, Rainer; Petersen, Kay U.; Schmid, Felix; Derlin, Thorsten; Koops, Andreas; Peine, Sven; Sterneck, Martina; Fischer, Lutz; Helmke, Knut
Summary Arterial neovascularization of liver grafts can be a source of significant blood loss during retransplantation. This study evaluated the effect of transcapsular arterial neovascularization on intraoperative blood loss during retransplantation and long‐term follow‐up. Eleven consecutive patients with transcapsular arterial neovascularization (seven male, four female; nine children, two adults; mean age 12.3 ± 16.3 years) and the same number of matched control patients were analysed. Blood loss was calculated based on transfusion requirements. The volume of transfused units of red blood cells per kilogram bodyweight until hepatectomy and during the entire procedure was significantly higher in patients with neovascularization than in control patients (0.32 ± 0.21 vs. 0.14 ± 0.11, and 0.94 ± 0.83 vs. 0.36 ± 0.38 respectively; P‐values 0.027). Neovascularization was associated with extensive intra‐abdominal adhesions and a longer operating time until hepatectomy (175.6 ± 52.1 min vs. 124.3 ± 34.9 min, P‐value 0.015). Postoperative revisions were performed more frequently in patients with neovessels. Graft survival did not differ between groups. Assessment for transcapsular arterial neovascularization should be included in preoperative Doppler ultrasound protocols to identify patients at risk of a complicated intra‐ and postoperative course in case of retransplantation.